PENGARUH RASIO LIKUIDITAS, LAVERAGE, OPERATING CAPACITY TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN COSMETICS AND HOUSEHOLD - Pertiwi, Rizki Novia; Hartono, Arif; Ulfah, Ika Farida (Jurnal Ekonomi Syariah Darussalam, 2022)
This study examines the effect of the independent variables namely Liquidity, Leverage, and Operating Capacity on Financial Distress. The subjects in this study were all Cosmetics and Household companies listed on the Indonesia Stock Exchange in 2016-2019. The method of determining the sample in this study uses the Purposive Sampling Method. The results of the research on the first hypothesis indicate that the liquidity variable has no effect on financial distress. This means that liquidity has a significant influence in predicting financial distress conditions because there is no significant difference in the liquidity of companies experiencing financial distress with companies not experiencing financial distress. The results of the research on the second hypothesis indicate that the variables of Leverage and Operating Capacity have an effect on Financial Distress. This means that if the company has high debt with a good level of debt management, it can finance the purchase of company assets to support the continuity of company activities and support inventory. The results of simultaneous testing of Liquidity, Leverage, and Operating Capacity variables have an effect on Financial Distress